UV-cured super-hydrophobic thermally conductive potting adhesive and electronic equipment

Through ultraviolet curing of superhydrophobic thermal potting, silicone oligomers and modified polymers combined with hydrophobically modified samarium-doped TiO2/BN fiber composites, the problems of high-temperature damage and composite applications of traditional thermal conductivity materials are solved, and the comprehensive effect of efficient thermal conductivity, superhydrophobicity and good mechanical properties are achieved.

CN117247760BActive Publication Date: 2025-04-11HYMN MATERIALS TECH SHENZHEN CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311522203.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-15
Publication Date
2025-04-11
Estimated Expiration
2043-11-15

AI Technical Summary

Technical Problem

Existing thermally conductive materials are prone to damage chips and electronic devices during high-temperature curing, and a single material is difficult to meet the needs of complex applications. Traditional processes have problems such as high energy consumption and filler deposition.

Method used

Ultraviolet curing superhydrophobic thermal potting glue is used to mix silicone oligomers, silicone modified polydimethylsiloxane and silicone modified polyurethane acrylate oligomers, hydrophobically modified samarium-doped ordered porous TiO2/BN fiber composite material and silicone nitride microwires are added as thermal fillers, and ultraviolet curing is carried out by combining appropriate auxiliary materials.

Benefits of technology

It achieves the improvement of efficient thermal conductivity, and has super-hydrophobic, moisture-proof and good mechanical properties, avoids high-temperature damage and filler deposition, reduces energy consumption and extends the service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an ultraviolet light-cured super-hydrophobic thermally conductive potting adhesive and an electronic device. The ultraviolet light-cured super-hydrophobic thermally conductive potting adhesive is prepared by using a mixture of an organosilicon oligomer, organosilicon-modified polydimethylsiloxane and organosilicon-modified polyurethane acrylate oligomer as a base, and adding thermally conductive fillers and auxiliary materials into the base; the auxiliary materials include a diluent, a leveling wetting agent, a catalyst, a photoinitiator, a coupling agent and a defoaming agent; the auxiliary materials may also include a flame retardant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermally conductive potting adhesives, and in particular to an ultraviolet light-cured super-hydrophobic thermally conductive potting adhesive and electronic equipment. Background Art

[0002] As the demand for computing power in the AI ​​field continues to increase, the core idea of ​​chiplet technology is to stack as many chips as possible within a short physical distance so that the information transmission speed between chips is fast enough. With the stacking of more chips, it has become a trend to continuously increase the packaging density. With the increase in packaging density, the power per unit circuit is also increasing to reduce circuit delay and increase operating speed. At the same time, the heat flux of chips and packaging modules is increasing, which significantly promotes the rapid development of advanced packaging technologies represented by chiplets and the demand for high-performance thermal conductive materials. In addition, the development of 5G has driven the increase in the value of thermal conductive materials for 5G mobile phones and the demand for thermal conductive materials for 5G base stations; at the same time, in the field of new energy vehicles, motor / electronic control systems and power battery systems have also put forward higher new demands on thermal conductive materials.

[0003] Since the focus of thermal conductive material performance in various fields (semiconductors, consumer electronics, automotive fields, etc.) is very different, the thermal conductive materials selected will also be different. In the semiconductor field, thermal conductive materials need to have high thermal conductivity and stability to ensure the normal operation of chips in high temperature environments; in the consumer electronics field, thermal conductive materials need to have good thermal conductivity, heat resistance, super hydrophobicity and chemical stability to ensure the normal operation of equipment and stability in underwater environments; in the automotive field, thermal conductive materials need to have high thermal conductivity, mechanical strength and corrosion resistance to cope with complex working conditions. However, a single thermal conductive material often cannot meet complex application requirements. The development and exploration of a new thermal conductive composite material that maintains high thermal conductivity while taking into account other comprehensive application requirements and material properties is the development trend of future applications of thermal conductive materials. In addition, the curing method of traditional thermal conductive packaging material processes is mainly high-temperature curing, which will damage products such as chips and electronic devices and shorten their service life. Summary of the invention

[0004] In order to solve the problems in the related art, the present invention provides a UV-curable super-hydrophobic thermally conductive potting adhesive and an electronic device.

[0005] In the first aspect, the present invention provides a UV-curable super-hydrophobic thermally conductive potting adhesive, which is prepared by using a mixture of silicone oligomers, silicone-modified polydimethylsiloxane, and silicone-modified polyurethane acrylate oligomers as a base, and adding thermally conductive fillers and auxiliary materials to the base; the auxiliary materials include diluents, leveling wetting agents, catalysts, photoinitiators, coupling agents, and defoaming agents; the auxiliary materials may also include flame retardants.

[0006] According to an embodiment of the present invention, the organosilicon oligomer is an organosilicon with a three-dimensional network structure with trifunctional silane as the main component, and is a general term for a series of oligomers such as organosilicon alkoxy oligomers, and can specifically be a methyl-type organosilicon alkoxy oligomer, a functional group-containing organosilicon oligomer, or an oligomer without an organic group, and the present invention does not limit this. For example, the organosilicon oligomer of the present invention can be a vinyl silane oligomer. Organosilicon-modified polydimethylsiloxane refers to a polydimethylsiloxane modified with a terminal hydroxyl group / terminated amino group silane oligomer. Organosilicon-modified polyurethane acrylate oligomer refers to a polyurethane acrylate oligomer modified with a terminal hydroxyl group / terminated amino group silane oligomer.

[0007] Silicone oligomers have the advantages of low surface tension, chemical resistance, excellent low-temperature flexibility and organic compatibility. Silicone modification is beneficial to improving the chemical resistance and high mechanical strength of the matrix, while also having high surface properties, which can maintain the good wear resistance, tear resistance and flexural resistance of polyurethane materials. At the same time, it has the advantages of good low-temperature flexibility and low surface tension, which can be better integrated and well embedded. In addition, silicone-modified UV-curable polyurethane acrylate oligomers have the advantages of UV curing and silicone materials, giving the base material the good properties of silicone materials, and at the same time have the advantages of fast curing speed and low energy consumption. Silicone-modified polydimethylsiloxane is a bifunctional and highly reactive silicone polymer with excellent softness, good solubility, high chemical stability and high mechanical strength.

[0008] The diluent is selected from ester diluents, preferably one or more of n-butyrate or isovalerate.

[0009] The leveling wetting agent is selected from one or more of acrylic or silicone leveling agents, preferably organic modified polysiloxane among silicone leveling agents.

[0010] The catalyst is selected from one or more of an organic tin compound or a platinum catalyst, preferably an organic tin compound.

[0011] The photoinitiator is selected from one or more of the alkyl phenones (α, α-diethoxyacetophenone, α-hydroxyalkyl phenone, α-aminoalkyl phenone), and the coupling agent is selected from one or more of the methacrylate silane coupling agent, vinyl silane coupling agent, and hydrogen-containing silicone oil coupling agent, preferably a vinyl silane coupling agent.

[0012] The flame retardant is one or more of organic nitrogen flame retardants and phosphorus flame retardants, which can produce a synergistic effect. Preferably, the flame retardant is composed of melamine and polyphosphate or melamine salt of pentaerythritol phosphate, cyclophosphamide polymer.

[0013] The defoamer is selected from one or more of an organosilicon type defoamer and a polyether modified organic type, and the organosilicon type defoamer is preferred.

[0014] According to an embodiment of the present invention, the thermally conductive filler includes a hydrophobically modified samarium-doped ordered porous TiO2 / BN fiber composite material, and the thermally conductive filler may also include a hydrophobically modified silicon nitride microwire. The thermally conductive filler may also be a one-dimensional linear or two-dimensional strip-shaped insulating thermally conductive material such as strip silicon nitride and linear silicon nitride.

[0015] According to an embodiment of the present invention, the hydrophobic modification treatment step is: dissolving dopamine hydrochloride and ethylene glycol in a mixture of Tris-HCl buffer solution and ethanol, stirring until completely dissolved, and adding a thermally conductive filler to the above solution and ultrasonically stirring.

[0016] According to an embodiment of the present invention, the method further includes: before the hydrophobic modification, placing the thermal conductive filler in a ball mill for ball milling; and / or the prepared UV light-cured super hydrophobic thermal conductive potting glue is subjected to mechanical orientation treatment before filling.

[0017] According to an embodiment of the present invention, the preparation steps of the samarium-doped ordered porous TiO2 / BN fiber composite material include: modifying polystyrene-acrylic nanoparticles and BN fibers using a CTAB solution; configuring butyl titanate and isopropanol into a solution in a ratio of 1:3, adding the modified BN fibers, and ultrasonically and vigorously stirring to obtain a BN fiber suspension; then dissolving SmCl3 in concentrated HCl, and slowly dripping it into the BN fiber suspension under vigorous stirring, adjusting the pH value to 4, continuously stirring the reaction, and obtaining a precursor sol solution; immersing the modified polystyrene-acrylic nanoparticles in the precursor sol solution, sealing and storing, and then filtering, washing, and drying, and then placing it in a muffle furnace for heat treatment, and then naturally cooling to room temperature to obtain a samarium-doped ordered porous TiO2 / BN fiber composite material, recorded as Sm-TiO2 / BN fiber composite material.

[0018] According to an embodiment of the present invention, the heat treatment steps are: heating to 200°C at a heating rate of 2°C / min, keeping warm for 1 hour, then heating to 460-1060°C at a heating rate of 10°C / min, keeping warm for 3 hours.

[0019] According to an embodiment of the present invention, the heat treatment steps are: heating to 200°C at a heating rate of 2°C / min, keeping warm for 1 hour, then heating to 1060°C at a heating rate of 10°C / min, and keeping warm for 3 hours.

[0020] According to an embodiment of the present invention, the composition comprises, by weight, 25-35 parts of organosilicon oligomer, 60-70 parts of organosilicon-modified polydimethylsiloxane, 25-35 parts of organosilicon-modified polyurethane acrylate oligomer, 7-10 parts of diluent, 3-4 parts of leveling wetting agent, 3-4 parts of catalyst, 5-8 parts of photoinitiator, 10-12 parts of coupling agent, 1.5-2.5 parts of flame retardant, 2 parts of defoaming agent, 155-245 parts of hydrophobically modified samarium-doped ordered porous TiO2 / BN fiber composite material, and 0-160 parts of hydrophobically modified silicon nitride microwires.

[0021] According to an embodiment of the present invention, in parts by weight, the composition includes 35 parts of silicone oligomer, 70 parts of silicone-modified polydimethylsiloxane, 35 parts of silicone-modified polyurethane acrylate oligomer, 10 parts of diluent, 4 parts of leveling wetting agent, 4 parts of catalyst, 8 parts of photoinitiator, 12 parts of coupling agent, 2 parts of flame retardant, 2 parts of defoaming agent, 245 parts of hydrophobically modified samarium-doped ordered porous TiO2 / BN fiber composite material, and 100 parts of hydrophobically modified silicon nitride microwires.

[0022] In a second aspect, the present invention provides a method for preparing a UV-curable super-hydrophobic thermally conductive potting adhesive.

[0023] Specifically, the preparation steps of the method for preparing the ultraviolet light-cured super-hydrophobic thermally conductive potting adhesive include:

[0024] Step 1: Preparation of samarium-doped ordered porous TiO2 / BN fiber composite materials.

[0025] Specifically, the synthesis of polystyrene-acrylic acid (PSA) nanoparticles as templates: 0.025g NaHCO3 and 0.1g 4-acrylic acid sodium salt hydrate were dissolved in 50mL deionized water, water bathed at 80°C, and vigorously stirred for 40min until completely dissolved. 5mL of polystyrene solution was added to the above solution, and after reacting for 1h, 0.025g of initiator ammonium persulfate or ammonium persulfate or sodium persulfate was added, and the reaction polymerization was continued for 20h. The resulting product was washed with n-hexane, isopropanol, and anhydrous ethanol in turn to obtain polystyrene-acrylic acid nanoparticles. The polystyrene-acrylic acid nanoparticles and BN fibers were modified using hexadecyltrimethylammonium bromide (CTAB) solution;

[0026] Prepare 1L solution of butyl titanate and isopropanol in a ratio of 1:3, add the modified BN fibers, and stir vigorously under ultrasonication for 30 min to obtain a BN fiber suspension. Dissolve 1.2 mol of SmCl3 in 30 ml of concentrated HCl and add Sm 3+ -HCl solution was slowly dripped into the above BN fiber suspension under vigorous stirring, the pH value of the total solvent system was adjusted to 4, and the reaction was stirred continuously for 1 h to obtain Sm 3+Doped BN fiber TiO2 precursor sol solution. The modified polystyrene-acrylic nanoparticle microsphere template is immersed in the precursor sol solution, sealed and stored for 3 days to allow the precursor sol solution to fully penetrate into the gaps of the microsphere template, then filtered, washed, dried, and placed in a muffle furnace for heat treatment at different temperatures, for example, heating to 200°C at a heating rate of 2°C / min, keeping warm for 1h, and then heating to 460-1060°C (preferably 1060°C) at a heating rate of 10°C / min, keeping warm for 3h, and naturally cooling to room temperature to obtain a samarium-doped ordered porous TiO2 / BN fiber composite material, recorded as Sm-TiO2 / BN fiber composite material.

[0027] It should be noted that the above steps are only described using the PSA template method as an example. Of course, direct chemical synthesis, or the use of other soft templates or hard template methods to prepare Sm-TiO2 / BN fiber composite materials can also be performed, and the present invention does not limit this.

[0028] Step 2: The samarium-doped ordered porous TiO2 / BN fiber composite material and one-dimensional silicon nitride microwire are modified to be hydrophobic and oleophilic.

[0029] Specifically, 3.84 g of dopamine hydrochloride and 160 μL of ethylene glycol were dissolved in 1 L of a mixture of Tris-HCl buffer solution and ethanol (volume: 3:1), stirred until completely dissolved, and the prepared Sm-TiO2 / BN fiber composite material and one-dimensional silicon nitride Si3N4 microwire were added to the above solution and ultrasonically stirred for 1 hour to obtain a hydrophobically modified Sm-TiO2 / BN fiber composite material and a hydrophobically modified one-dimensional silicon nitride Si3N4 microwire.

[0030] Step three: add silicone oligomer, silicone modified polydimethylsiloxane, silicone modified polyurethane acrylate oligomer to the stirrer, evacuate at room temperature, stir at low speed first and then at high speed, then add the modified Sm-TiO2 / BN fiber composite material, or the modified Sm-TiO2 / BN fiber composite material and modified one-dimensional silicon nitride Si3N4 micron wire mixed filler to the above prepolymer, continue stirring for 1 hour, then add active diluent, leveling wetting agent, catalyst, silane coupling agent, flame retardant, defoaming agent to the above mixture, evacuate, stir at 400-500 rpm for 0.5h, then stir at 700-800 rpm for 1h to mix the system evenly; then add photoinitiator, control the temperature below 40°C, evacuate, and stir vigorously at high speed for 1h to obtain UV light solid super hydrophobic thermal conductive potting glue.

[0031] In a third aspect, the present invention provides an electronic device, comprising the UV light-cured super-hydrophobic thermally conductive potting adhesive as described in any one of the first aspects.

[0032] The technical solution provided by the present invention may include the following beneficial effects:

[0033] The ultraviolet light-cured super-hydrophobic thermally conductive potting glue provided by the present invention first uses a template method to prepare an ordered porous structure TiO2 / BN fiber composite material. This structure adopts a point-surface combination design concept. The TiO2 spherical porous structure improves the specific surface area and chemical stability of the composite material, adjusts the dielectric properties of the BN fiber and enhances the mechanical properties; at the same time, it improves the composite material's response to ultraviolet light and the absorption of ultraviolet photons, promotes the propagation of internal phonons, and thus improves the thermal conductivity. Furthermore, the samarium-doped ordered porous TiO2 / BN composite material increases the transmission channel of internal phonons and shortens the transmission distance, thereby further improving the heat transfer rate inside the composite material. Subsequently, silicone oligomers and silicone-modified UV-curable resins (silicone-modified polydimethylsiloxane, silicone-modified polyurethane acrylate oligomers) are used as the base, samarium-doped ordered porous TiO2 / BN composite materials are mixed as thermal conductive fillers and other auxiliary materials to prepare UV-cured thermal conductive potting glue. Under the action of ultraviolet light, the charge transfer complex is excited, so that the silicone oligomers, silicone-modified UV-curable resins and photoinitiators are combined and cross-linked to form a curing system. Compared with traditional thermal curing, on the one hand, the volume and mass loss of the potting glue formed by light curing are small, which is conducive to improving product quality and can solve the impact of temperature on the damage of electronic components during use; on the other hand, its rapid curing reduces the deposition of fillers in the composite material and reduces energy consumption; furthermore, it can have a good penetration effect on the gap before curing, so the flexibility, weather resistance and bonding strength of the potting glue itself can also meet the needs of direct use after curing. In the future, mass production of design freedom and customization needs can be effectively realized. Furthermore, after the samarium-doped ordered porous TiO2 / BN fiber composite material is modified to be hydrophobic and oleophilic, on the one hand, it can strengthen the interface contact between the composite material and the silicone-modified UV-curable resin, which is beneficial to the UV-curing reaction and enhances the thermal conductivity of the potting compound. On the other hand, it also achieves the super-hydrophobic property of the potting compound, avoiding the influence of water molecules on the internal fillers, especially the fillers that are easily hydrolyzed, which is of great significance to improving the reliability of the product. In addition, the potting compound has super-hydrophobic and moisture-proof properties, and at the same time, it also avoids the failure or damage of chips and electronic devices due to erosion by moisture in the air, shortening their service life, and can also be used for the waterproof performance requirements of electronic products in deep water areas.

[0034] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. DETAILED DESCRIPTION

[0035] The present invention is further described below by way of examples, but it is to be understood that these specific examples will not limit the scope of the present invention in any way. It should be noted that, unless otherwise specified, the raw materials used in the following examples are all commercially available products.

[0036] Example 1: 0.025g NaHCO3 and 0.1g 4-acrylic acid sodium salt hydrate were dissolved in 50mL deionized water, heated in a water bath at 80°C, and stirred vigorously for 40min until completely dissolved. 5mL polystyrene solution was added to the above solution, reacted for 1h, and then 0.025g initiator ammonium persulfate or ammonium persulfate or sodium persulfate was added, and the reaction polymerization was continued for 20h. The obtained product was washed with n-hexane, isopropanol, and anhydrous ethanol in turn to obtain polystyrene-acrylic acid nanoparticles. The polystyrene-acrylic acid nanoparticles and BN fibers were modified using CTAB solution.

[0037] Prepare 1L solution of butyl titanate and isopropanol in a ratio of 1:3, add the modified BN fibers, and stir vigorously under ultrasonication for 30 min to obtain a BN fiber suspension. Dissolve 1.2 mol of SmCl3 in 30 ml of concentrated HCl and add Sm 3+ -HCl solution was slowly dripped into the above BN fiber suspension under vigorous stirring, the pH value of the total solvent system was adjusted to 4, and the reaction was stirred continuously for 1 h to obtain Sm 3+ Doped BN fiber TiO2 precursor sol solution. The modified polystyrene-acrylic nanoparticle microsphere template is immersed in the precursor sol solution, sealed and stored for 3 days to allow the precursor sol solution to fully penetrate into the gaps of the microsphere template, then filtered, washed, dried, and placed in a muffle furnace for heat treatment at different temperatures, for example, heating to 200°C at a heating rate of 2°C / min, keeping warm for 1h, then heating to 460°C at a heating rate of 10°C / min, keeping warm for 3h, and naturally cooling to room temperature to obtain a samarium-doped ordered porous TiO2 / BN fiber composite material, recorded as Sm-TiO2 / BN fiber composite material.

[0038] Example 2: Different from Example 1, in the heat treatment step, the temperature is increased to 200°C at a heating rate of 2°C / min, kept at this temperature for 1 hour, then increased to 660°C at a heating rate of 10°C / min, kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain a samarium-doped ordered porous TiO2 / BN fiber composite material, denoted as Sm-TiO2 / BN fiber composite material.

[0039] Example 3: Different from Example 1, in the heat treatment step, the temperature is increased to 200°C at a heating rate of 2°C / min, kept at this temperature for 1 hour, then increased to 860°C at a heating rate of 10°C / min, kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain a samarium-doped ordered porous TiO2 / BN fiber composite material, denoted as Sm-TiO2 / BN fiber composite material.

[0040] Example 4: Different from Example 1, in the heat treatment step, the temperature is increased to 200°C at a heating rate of 2°C / min, kept at this temperature for 1 hour, then increased to 1060°C at a heating rate of 10°C / min, kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain a samarium-doped ordered porous TiO2 / BN fiber composite material, recorded as Sm-TiO2 / BN fiber composite material.

[0041] Example 5: Dissolve 3.84 g of dopamine hydrochloride and 160 μL of ethylene glycol in 1 L of a mixture of Tris-HCl buffer solution and ethanol (volume: 3:1), stir until completely dissolved, add the Sm-TiO2 / BN fiber composite material prepared in Example 4 to the above solution, and stir ultrasonically for 1 hour to obtain a hydrophobically modified Sm-TiO2 / BN fiber composite material.

[0042] In parts by weight, 25 parts of silicone oligomer, 60 parts of silicone-modified polydimethylsiloxane, and 25 parts of silicone-modified polyurethane acrylate oligomer are added to a stirrer, vacuumed at room temperature, stirred at low speed first and then at high speed, and then 155 parts of modified Sm-TiO2 / BN fiber composite materials are added to the above prepolymer, and stirring is continued for 1 hour, and then 7 parts of active diluent, 3 parts of leveling wetting agent, 3 parts of catalyst, 10 parts of silane coupling agent, and 2 parts of defoaming agent are added to the above mixture, vacuumed, stirred at 400-500 rpm for 0.5h, and then stirred at 700-800 rpm for 1h to mix the system evenly; then 5 parts of photoinitiator are added, the temperature is controlled below 40°C, vacuumed, and stirred vigorously at high speed for 1h to obtain UV-curable super hydrophobic thermal conductive potting glue.

[0043] Example 6: Different from Example 5, the addition amount of the modified Sm-TiO2 / BN fiber composite material is adjusted to 185 parts.

[0044] Example 7: Different from Example 5, 35 parts of silicone oligomer, 70 parts of silicone-modified polydimethylsiloxane, and 35 parts of silicone-modified polyurethane acrylate oligomer are added to a stirrer, evacuated at room temperature, stirred at low speed first and then at high speed, and then 215 parts of modified Sm-TiO2 / BN fiber composite materials are added to the above prepolymer, and stirring is continued for 1 hour. Then 10 parts of active diluent, 4 parts of leveling wetting agent, 4 parts of catalyst, 12 parts of silane coupling agent, and 2 parts of defoaming agent are added to the above mixture, evacuated, stirred at 400-500 rpm for 0.5h, and then stirred at 700-800 rpm for 1h to mix the system evenly; then 8 parts of photoinitiator are added, the temperature is controlled below 40°C, evacuated, and stirred vigorously at high speed for 1h to obtain UV-curable super hydrophobic thermal conductive potting glue.

[0045] Example 8: Different from Example 7, the addition amount of the modified Sm-TiO2 / BN fiber composite material is adjusted to 245 parts.

[0046] Example 9: Different from Example 8, after adding 10 parts of active diluent, 4 parts of leveling wetting agent, 4 parts of catalyst, 12 parts of silane coupling agent, 2 parts of defoaming agent to the above mixture, 1.5 parts of flame retardant are also added.

[0047] Example 10: Different from Example 9, the amount of flame retardant added is adjusted to 2 parts.

[0048] Example 11: Different from Example 9, the amount of flame retardant added is adjusted to 2.5 parts.

[0049] Example 12: Dissolve 3.84 g of dopamine hydrochloride and 160 μL of ethylene glycol in 1 L of a mixture of Tris-HCl buffer solution and ethanol (volume: 3:1), stir until completely dissolved, add the Sm-TiO2 / BN fiber composite material and one-dimensional silicon nitride Si3N4 micron wire prepared in Example 4 to the above solution, and stir ultrasonically for 1 hour to obtain a hydrophobically modified Sm-TiO2 / BN fiber composite material and a hydrophobically modified one-dimensional silicon nitride Si3N4 micron wire.

[0050] In parts by weight, 35 parts of silicone oligomer, 70 parts of silicone-modified polydimethylsiloxane, and 35 parts of silicone-modified polyurethane acrylate oligomer are added to a stirrer, vacuumed at room temperature, stirred at low speed first and then at high speed, and then 245 parts of modified Sm-TiO2 / BN fiber composite materials and 40 parts of modified one-dimensional silicon nitride Si3N4 micron wires are added to the above prepolymer, and stirring is continued for 1 hour. Then 10 parts of active diluent, 4 parts of leveling wetting agent, 4 parts of catalyst, 12 parts of silane coupling agent, 2 parts of flame retardant, and 2 parts of defoaming agent are added to the above mixture, vacuumed, stirred at 400-500 rpm for 0.5h, and then stirred at 700-800 rpm for 1h to mix the system evenly; then 8 parts of photoinitiator are added, the temperature is controlled below 40°C, vacuumed, and stirred vigorously at high speed for 1h to obtain UV-curable super hydrophobic thermal conductive potting glue.

[0051] Example 13: Different from Example 12, the amount of modified one-dimensional silicon nitride Si3N4 micrometer wire added is adjusted to 100 parts.

[0052] Example 14: Different from Example 12, the amount of modified one-dimensional silicon nitride Si3N4 micrometer wire added is adjusted to 160 parts.

[0053] Example 15: 245 parts of Sm-TiO2 / BN fiber composite materials and 100 parts of one-dimensional silicon nitride Si3N4 micron wires prepared in Example 4 were put into a high-speed ball mill for ball milling for 1 hour, and then dried for use. Then, a modification treatment was performed, that is, 3.84g of dopamine hydrochloride and 160μL of ethylene glycol were dissolved in 1L of a mixture of Tris-HCl buffer solution and ethanol (volume ratio of 3:1), stirred until completely dissolved, and the mixture of the ball-milled Sm-TiO2 / BN fiber composite material and one-dimensional silicon nitride Si3N4 micron wire was added to the above solution, and ultrasonically stirred for 1 hour to obtain a mixture of a hydrophobically modified Sm-TiO2 / BN fiber composite material and a hydrophobically modified one-dimensional silicon nitride Si3N4 micron wire.

[0054] In parts by weight, 35 parts of organosilicon oligomer, 70 parts of organosilicon-modified polydimethylsiloxane, and 35 parts of organosilicon-modified polyurethane acrylate oligomer are added to a stirrer, vacuumized at room temperature, stirred at a low speed first and then at a high speed, and then 245 parts of a mixture of modified Sm-TiO2 / BN fiber composite material and 100 parts of a mixture of modified one-dimensional silicon nitride Si3N4 micron wires are added to the above prepolymer, and stirring is continued for 1 hour, and then 10 parts of an active diluent, 4 parts of a leveling wetting agent, 4 parts of a catalyst, 12 parts of a silane coupling agent, 2 parts of a flame retardant, 2 parts of defoaming agent are added to the above mixture, vacuumized, stirred at 400-500 rpm for 0.5 h, and then stirred at 700-800 rpm for 1 h to mix the system evenly; then 8 parts of photoinitiator are added, the temperature is controlled below 40°C, vacuumized, and vigorously stirred at high speed for 1 h. The obtained potting glue is subjected to mechanical orientation treatment to obtain UV light-cured super hydrophobic thermal conductive potting glue.

[0055] The samples prepared in Examples 1-4 were mixed with paraffin wax in a certain ratio, heated, melted, stirred and poured into a mold, and then taken out after cooling to obtain a 10mm×3mm×2mm sample. The samples prepared in Examples 5-15 were placed in a mold, and cured under ultraviolet light to obtain a 10mm×3mm×2mm sample. The thermal conductivity of the above samples in the material thickness direction was measured according to ASTM D5470.

[0056] The hydrophobicity is tested by contact angle: the static contact angle between the device surface and water is tested at room temperature, cosθ=(δ SV -δ SL ) / δ LV . (Note: SV ,δ SL and δ LV are the interfacial tensions between solid and gas, solid and liquid, and liquid and gas, respectively. θ is the contact angle when the solid, liquid, and gas are in equilibrium. When θ < 90°, it is hydrophilic; when θ > 90°, it is hydrophobic; when θ < 5°, it is a superhydrophilic surface; when θ > 120°, it is a superhydrophobic surface. ).

[0057] Flexibility: After folding the label material three times, observe whether the sample is cracked.

[0058] The test was carried out in accordance with GB / T 528-2008, and the tensile properties were measured on an electronic tensile testing machine (tensile speed 500 mm / min, test temperature room temperature).

[0059] The thermal conductivity, hydrophobicity, flame retardancy and mechanical properties of the samples 1-15 prepared in the above examples are shown in the following table:

[0060]

[0061] From the data in the table above, it can be seen that for samples 1-4, as the sintering temperature increases, the thermal conductivity and mechanical properties of the samples gradually improve. When the temperature is 1060°C, the performance of the composite material reaches the best. Since the boron nitride rings inside the composite material after high temperature treatment are arranged between the fiber layers along the parallel axis, the secondary growth of the grains and the development of directional grain arrangement are promoted, which improves the mechanical properties and thermal conductivity of the fiber. At the same time, the coating of titanium dioxide further improves the chemical stability and mechanical properties of the composite material. Further, from the data of samples 5-8, it can be seen that with the increase of the thermal conductive filler content, the thermal conductivity, hydrophobicity, mechanical properties and flexibility of the samples are significantly enhanced. From the data of samples 9-11, it is shown that the addition of flame retardant improves the flame retardant grade of the material (when the flame retardant is 2.0 parts, the flame retardant grade is V-0), but the thermal conductivity, hydrophobicity, mechanical properties and flexibility of the material have no obvious effect. Furthermore, the test data of samples 12-14 showed that the increase of one-dimensional Si3N4 micrometer wires of thermal conductive auxiliary material further improved the thermal conductivity, mechanical properties and hydrophobicity of the material, but the excessive filling amount caused the filler to agglomerate and be difficult to disperse, thereby reducing the thermal conductivity and mechanical properties of the material (data of sample 14). In order to further improve the thermal conductivity and mechanical properties of the material, based on sample 13, the prepared potting glue was mechanically oriented and then cured, and its thermal conductivity and mechanical properties were significantly improved (data of sample 15).

[0062] The above description is only a preferred embodiment of the present invention and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present invention is not limited to the technical solution formed by a specific combination of the above technical features, but also should cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with the technical features with similar functions disclosed in the present invention (but not limited to) to form a technical solution.

Claims

1. A UV-curable super-hydrophobic thermally conductive potting adhesive, characterized in that: The invention discloses a thermal conductive filler and a plurality of auxiliary materials, which are prepared by using a mixture of an organosilicon oligomer, an organosilicon-modified polydimethylsiloxane and an organosilicon-modified polyurethane acrylate oligomer as a base, and adding thermal conductive fillers and auxiliary materials into the base; the auxiliary materials include a diluent, a leveling wetting agent, a catalyst, a photoinitiator, a coupling agent and a defoaming agent; the thermal conductive filler includes a hydrophobically modified samarium-doped ordered porous TiO2 / BN fiber composite material; The organosilicon-modified polydimethylsiloxane refers to polydimethylsiloxane modified with terminal hydroxyl group / terminal amino group silane oligomer.

2. The ultraviolet light curable super hydrophobic thermal conductive potting adhesive according to claim 1, characterized in that: The thermally conductive filler also includes hydrophobically modified silicon nitride microwires.

3. The ultraviolet light curable super hydrophobic thermal conductive potting adhesive according to claim 2, characterized in that: The hydrophobic modification treatment steps are: dissolving dopamine hydrochloride and ethylene glycol in a mixture of Tris-HCl buffer solution and ethanol, stirring until completely dissolved, and adding a thermal conductive filler into the solution and stirring ultrasonically.

4. The ultraviolet light curable super hydrophobic thermal conductive potting adhesive according to claim 3, characterized in that: Also includes: Before the hydrophobic modification, the thermal conductive filler is placed in a ball mill for ball milling; And / or, the prepared UV light-cured super-hydrophobic thermally conductive potting adhesive is subjected to mechanical orientation treatment before filling.

5. The ultraviolet light curable super hydrophobic thermal conductive potting adhesive according to claim 2, characterized in that: The preparation steps of the samarium-doped ordered porous TiO2 / BN fiber composite material include: modifying polystyrene-acrylic nanoparticles and BN fibers using a CTAB solution; preparing a solution of butyl titanate and isopropanol in a ratio of 1:3, adding the modified BN fibers, and stirring them vigorously under ultrasound to obtain a BN fiber suspension; then dissolving SmCl3 in concentrated HCl, and slowly dripping it into the BN fiber suspension under vigorous stirring, adjusting the pH value to 4, and continuously stirring the reaction to obtain a precursor sol solution; immersing the modified polystyrene-acrylic nanoparticles in the precursor sol solution, sealing and storing, then filtering, washing, drying, and then placing it in a muffle furnace for heat treatment, and then naturally cooling it to room temperature to obtain a samarium-doped ordered porous TiO2 / BN fiber composite material, which is recorded as Sm-TiO2 / BN fiber composite material.

6. The ultraviolet light curable super hydrophobic thermal conductive potting adhesive according to claim 5, characterized in that: The heat treatment steps are: heating to 200°C at a heating rate of 2°C / min, keeping the temperature for 1 hour, then heating to 460-1060°C at a heating rate of 10°C / min, and keeping the temperature for 3 hours.

7. The ultraviolet light curable super hydrophobic thermal conductive potting adhesive according to claim 6, characterized in that: The heat treatment steps are: heating to 200°C at a heating rate of 2°C / min, keeping the temperature for 1 hour, then heating to 1060°C at a heating rate of 10°C / min, and keeping the temperature for 3 hours.

8. The ultraviolet light curable super hydrophobic thermal conductive potting adhesive according to claim 2, characterized in that: Calculated in parts by weight, the invention comprises 25-35 parts of organosilicon oligomer, 60-70 parts of organosilicon modified polydimethylsiloxane, 25-35 parts of organosilicon modified polyurethane acrylate oligomer, 7-10 parts of diluent, 3-4 parts of leveling wetting agent, 3-4 parts of catalyst, 5-8 parts of photoinitiator, 10-12 parts of coupling agent, 0-2.5 parts of flame retardant, 2 parts of defoaming agent, 155-245 parts of hydrophobically modified samarium doped ordered porous TiO2 / BN fiber composite material, and 0-160 parts of hydrophobically modified silicon nitride microwire.

9. The ultraviolet light curable super hydrophobic thermal conductive potting adhesive according to claim 8, characterized in that: Measured in parts by weight, the composition includes 35 parts of organosilicon oligomer, 70 parts of organosilicon modified polydimethylsiloxane, 35 parts of organosilicon modified polyurethane acrylate oligomer, 10 parts of diluent, 4 parts of leveling wetting agent, 4 parts of catalyst, 8 parts of photoinitiator, 12 parts of coupling agent, 2 parts of flame retardant, 2 parts of defoaming agent, 245 parts of hydrophobically modified samarium doped ordered porous TiO2 / BN fiber composite material, and 100 parts of hydrophobically modified silicon nitride microwires.

10. An electronic device comprising the UV light-cured super-hydrophobic thermally conductive potting adhesive according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • UV adhesive for sealing quantum dot material, and preparation method thereof

    CN105441012A

  • Radiation curable quantum dot material sealant composition

    CN107556964A